Performance Evaluation of Different Seed Cotton Distribution Systems used in Modern Indian Ginneries - Shukla, S K; Arude, V G; Nath, Jyoti M (Journal of Agricultural Engineering, 2010)
The distribution systems were compared on the basis of productivity of double roller gins and power requirements. The productivity loss of first, central and end DR gins in a row with the distribution system varied between 2.7 to 9.6% as compared to manual feeding. However, the trolley feeding-single side for 6 DR gins / trolley did not cause any productivity loss. Among the systems studied, the trolley feeding-single side for 6 DR gins / trolley was best, followed by trolley distribution system-either side (8 DR gins/trolley) in terms of productivity of DR gins. In case of screw conveyor distribution system, minimum productivity loss was observed for 9 DR gins. Power requirement per DR gin for different kind of distribution systems varied from 373 to 1343 W. Minimum power requirement occured for trolley feeding system-either side with 18 DR gins/trolley, whereas maximum power requirement was for trolley distribution system-single side with 6 DR gins / trolley. The distribution systems should be carefully selected and used for feeding the optimum number of DR gins so as to avoid the shortage of seed cotton while processing.